2014
DOI: 10.1002/oby.20904
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of weight change in black Americans: Pooled analysis from three behavioral weight loss trials

Abstract: ObjectiveDifferentiating trajectories of weight change and identifying associated baseline predictors can provide insights for improving behavioral obesity treatment outcomes.Design and MethodsSecondary, observational analyses using growth mixture models were conducted in pooled data for 604 black American, primarily female adults in three completed clinical trials. Covariates of identified patterns were evaluated.ResultsThe best fitting model identified three patterns over 2 years: 1) mean weight loss of appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 36 publications
(44 reference statements)
3
24
1
Order By: Relevance
“…Many of the past studies reviewed earlier also supported three patterns of weight loss over time: modest loss, moderate loss, and substantial loss . The current investigation used a larger number of parameters to derive groups, but the latent class analyses similarly supported a three‐group model.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Many of the past studies reviewed earlier also supported three patterns of weight loss over time: modest loss, moderate loss, and substantial loss . The current investigation used a larger number of parameters to derive groups, but the latent class analyses similarly supported a three‐group model.…”
Section: Discussionmentioning
confidence: 55%
“…Three latent groups were derived: modest loss‐complete regain (7% loss at 6 months), intermediate loss‐minimal regain (14%), and substantial loss‐minimal regain (22%). Another study , examining weight loss outcomes over 2 years, also supported three similar weight loss trajectories in a large sample of African‐American women across multiple lifestyle interventions. Although percent weight loss was not recorded, three distinct weight loss trajectories were supported: modest loss and regain, modest and consistent loss, and substantial and consistent loss.…”
Section: Introductionmentioning
confidence: 72%
“…and length (1 to 4 yrs.) of behavioral interventions, health status of participants, and type of analytic approaches applied (cluster, principle component, or latent profile analysis) (47). Despite differences in intervention length, frequency of contact, type of diet etc., several previous studies have identified distinct patterns of weight change over time, in general agreement with our results; however, the exact patterns of weight change vary across studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, the literature on this topic is limited and has employed a variety of approaches to identify weight change patterns, diverse samples, and considered a limited number of behavioral factors. These include cluster analysis (4), principal components analysis (5, 6), and latent class analysis (7) over time frames ranging from 12 weeks (4) to 2 years (7). Samples have been comprised of African American women (7), individuals with type 2 diabetes (5, 6), or in a high proportion of individuals with pre-diabetes and/or metabolic syndrome (4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation